2010
DOI: 10.1097/mpg.0b013e3181d98e45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bifidobacterium lactis HN019 and Prebiotic Oligosaccharide Added to Milk on Iron Status, Anemia, and Growth Among Children 1 to 4 Years Old

Abstract: Preschoolers are usually fed milk, which has good acceptance and can be easily fortified for delivery of probiotics. Consumption of B lactis HN019 and prebiotic-fortified milk resulted in a smaller number of iron-deficient preschoolers and increased weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(111 citation statements)
references
References 42 publications
2
106
0
2
Order By: Relevance
“…This is especially true for the group of B vitamins [85,86]. Furthermore, pro-and prebiotics can promote absorption of minerals like magnesium, iron, and calcium [87][88][89]. This may be due to increased SCFA production, which decreases intestinal pH and promotes epithelial health leading to increased mineral solubility and uptake [90].…”
Section: Pre- Pro- and Antibioticsmentioning
confidence: 99%
“…This is especially true for the group of B vitamins [85,86]. Furthermore, pro-and prebiotics can promote absorption of minerals like magnesium, iron, and calcium [87][88][89]. This may be due to increased SCFA production, which decreases intestinal pH and promotes epithelial health leading to increased mineral solubility and uptake [90].…”
Section: Pre- Pro- and Antibioticsmentioning
confidence: 99%
“…There is also some evidence that probiotic can enhance bioavailability of iron. Human studies have been performed to discover underlying mechanism of probiotic effect on iron status, such as creating an acidic environment in the intestinal tract which makes iron more absorbable, making iron biologically available by producing iron-chelating ligands, or degrading mineral complexing phytic acid from food [13][14][15]. Therefore, making probiotics a part of a diet plan, can prevent and ameliorate iron deficiency anemia in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Many Bifidobacterium species are not inhibited by the bacteriostatic properties of lactoferrin, and the growth of some is actually enhanced in the presence of lactoferrin (Kim et al 2004). A recent study has shown that the addition of Bifidobacterium species to milk as a probiotic decreases the incidence of iron deficiency in young children (Sazawal et al 2010). Although the mechanism for this effect is unknown, it was suggested that the use of probiotics could reduce enteric infections resulting in better iron absorption.…”
Section: Iron Absorption During Sucklingmentioning
confidence: 97%